A model-driven approach for transforming GRAFCET specification into PLC code including hierarchical structures. Issue 13 (2019) - Julius, Robert; Trenner, Thomas; Neidig, Joerg; Fay, Alexander
Abstract: GRAFCET, as defined in IEC 60848, is a powerful graphical modelling language to define the behavior of sequence controls with discrete event systems. In contrast to other specifications languages, one of the main advantages of GRAFCET is the specification of hierarchical structures. Therefore, distributed and nested program parts within a control application can be described by enclosing steps, partial-Grafcet and forcing orders. This contribution presents a meta-driven approach to transform GRAFCET specifications, including hierarchical structures, to Structured Text (ST), an IEC 61131-3 control programming language. To exactly meet the GRAFCET evolution rules and to mimic the specified behavior of the sequential control specification, an interpretation algorithm has been defined. The concept has been validated by means of an application example.